Teacher Professional Development to Train Digital Skills with Technological Pedagogical Content Knowledge (TPACK) - Ardi Nugraha, Christophorus; Kuswandi, Dedi; Praherdhiono, Henry (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2022)
During the Covid-19 pandemic, the trend of blended learning increased rapidly. The Indonesian government provides various supporting facilities for blended learning, one of them is a learning account. Unfortunately, this surge in demand for and provision of supporting facilities has not been matched by sufficient skills to properly organize online learning. Many teachers do not know how to utilize ICT in learning. The author took the initiative to develop teacher professional development activities to improve digital skills. These activities were developed using the technological Pedagogical Content Knowledge (TPACK) and using the Analyze, Design, Develop, Implement, Evaluate (ADDIE) model. It can be concluded that these activities can be duplicated again with some adjustments. First, this training is suitable for teachers at the K12 level. If it will be used for PAUD/TK teachers, this training needs to be redesigned. Second, it would be much better if the institution where the teacher works provide dedicated hours for professional development which are also counted into teaching/additional teacher hours.